Keseimbangan Pasar Monopoli dalam Teori Permintaan dan Penawaran Serta Dampaknya Terhadap Kesejahteraan Sosial - Sarah Ramadhani; Ribka Melisa V Manullang; Tri Karunia Angel Br Purba (Jurnal Mutiara Ilmu Akuntansi, 2025)
This paper discusses the equilibrium of the monopoly market within the framework of the theory of demand and supply, and how it impacts social welfare. In a monopoly market, there is one seller who controls the entire supply of a good and service, which allows the monopoly company to influence the price and quantity of goods produced. This study uses Qualitative Methods to analyze the interaction between demand and supply in a monopoly market, focusing on how higher pricing and limited production reduce consumer surplus and create market imbalances. In addition, this study also explores the negative impacts of the monopoly market on social welfare, where imbalances in the distribution of goods and services can lead to a decrease in the quality of life of the community. The results of the study show that although monopoly companies can achieve greater profits, consumers and society as a whole tend to be disadvantaged, with inefficient allocation of resources and unfair distribution.